Morphological and anatomical characteristics of some plant species of lauraceae family collected in inland sandy area of Phong Dien town, Hue city - Truong, Thi Hieu Thao; Phung, Thi Bich Hoa; Nguyen, Thi Hoai Thuong; Nguyen, Thi Thuy (Hue University Journal of Science: Natural Science, 2025)
This study examines with the morphological and anatomical characteristics of three species in the Lauraceae family that grow in the inland sandy area of Phong Dien Town, Hue City. The analysis reveals that all three species exhibit traits typical of strongly heliophilous plants, as reflected in the morphology and anatomy of their vegetative organs. Notable features include well-developed palisade parenchyma, a thick cork layer covering the stems and roots, providing thermal insulation, and numerous xylem vessels with narrow lumens, which enhance water absorption under arid conditions. The findings are valuable data for the botanical database of this ecologically unique region and provide a scientific basis for the conservation and restoration of plant cover in the inland sandy zones of the locality.